PENGARUH BRAND TRUST TERHADAP NIAT KONSUMEN UNTUK MELAKUKAN PEMBELIAN PRODUK ELEKTRONIK PADA SITUS JUAL BELI LAZADA - Riski Taufik Hidayah (UPT Penerbitan Universitas Jember)
This study aimed to determine the responses of consumers on brand trust and purchase intentions and to determine how much influence brand trust on the intention to buy electronic goods online at trading site Lazada. The method used is descriptive and verification method with data collection via questionnaires. Sample was obtained by the technique of problem-solving research. Spearman Rank Correlation Coefficient analysis, determination coefficient and hypothesis testing via t test used in this study. Based on Spearman Rank correlation values obtained correlation of 0.539. This means that the Brand Trust relationships were with Intent to Buy. While the influence of brand trust on purchase intentions by 29.05% and the remainder is equal to 70.95% influenced by several variables or other. This study makes several recommendations: (1) the Company shall pay attention to the speed in responding to complaints - complaints from consumers through the addition of customer service in order to respond to consumer complaints quickly. (2) The company must provide continuous information about the latest electronic goods, so that consumers do not seek information to other e-commerce through advertising in media such as magazines or other online media and even television.